How many CDs do you have?: The impact of teaching-materials on formulaic language processing in Japanese learners of English - Julian, Northbrook (2020)
Formulaic sequences are processed more quickly and sound more natural than matched non-formulaic language for native speakers. However, little is known about how the speeded processing and intuitions about naturalness emerge and develop in second language learners, especially at the early stages. The research presented in this thesis explores, from a usage-based perspective, the relationship between the input in teaching materials and the development of a processing advantage in Japanese learners of English for a type of formulaic language: ‘lexical bundles’, which are frequently occurring sequences of words that may constitute a complete utterance (e.g., I don’t really know) but often do not (e.g., in the middle of). Using a corpus-based approach, Study 1 compared the most frequent lexical bundles in Japanese junior high school English textbooks with a native-speaker reference corpus and asked whether they were quantitatively and qualitatively representative of those found in conversational English. Overall, lexical bundles were found to be very frequent in the textbooks, but they deviated considerably from native-speaker language in terms of their frequency distribution. Study 2 used a ‘phrasal judgment’ task to assess the extent that the textbook materials impact upon processing for the students exposed them. Students responded to lexical bundles from their textbooks significantly faster and more accurately compared to control items (e.g., going to visit vs going to say). They were also sensitive to the frequency of occurrence in their textbooks in a continuous manner – i.e., lower frequency items were responded to slower, and higher frequency items faster, across the frequency continuum. Study 3 explored the perceived naturalness of lexical bundles using an offline naturalness rating task and compared performance by a group of adult Japanese learners of English and native English speakers. Naturalness ratings from both groups were predicted by frequency of occurrence, once again in a continuous manner. However, the Japanese English learners were sensitive to textbook frequency, and the native speakers to frequency counts from the British National Corpus. Study 4 used a repetitive phrasal judgment task, combined with exposure to lexical bundles, either in an ‘enhanced’ (by underlining) or ‘hidden’ (i.e., no enhancement) condition, in constructed materials. The study showed that repetition facilitated processing, and further that there was an initial, but short lived, benefit for textual enhancement. The results also demonstrated that processing behaviour changed after just one exposure to items, and further a post-test conducted one week later indicated that students retained knowledge of the lexical bundles. Overall the results from the studies presented in this thesis provide a valuable new perspective on how a processing advantage for formulaic sequences emerges in reaction to input; in this case due to teaching materials. The fact that even early-stage EFL learners display a formulaic advantage for sequences extracted from their learning materials, and that this remains years after encountering these materials, suggests that very careful consideration needs to be given to the quality of the materials we present students. Crucially, the findings call into question prior claims that L2 learners process language in a word-by-word, computational manner, or else that formulaic processing only emerges at higher proficiency levels. Notably, the set of findings support a ‘usage-based’ model of language development, whereby processing develops incrementally, with each and every exposure to a sequence of words in second language speakers.